Radiological and Clinicopathological Profiles Between Early- versus Advanced-Stage of Breast Cancer: a Single-Centre Comparative Study - Latief, Shofiyah; Kartika, Andy Visi (Journal of Neonatal Surgery, 2025)
Introduction: Breast cancer remains a leading cause of morbidity and mortality among women worldwide, with significant clinical and pathological differences between early and advanced stages. Understanding these differences is crucial for improving diagnosis and treatment strategies. Methods: This cross-sectional, descriptive correlational study reviewed 40 medical records of female breast cancer patients treated at Ibnu Sina Hospital, Makassar. Patients were divided into early-stage (n=20) and advanced-stage (n=20) groups. Clinical, radiological, and histopathological data were collected, including tumor size, lymph node involvement, hormone receptor status, HER2 expression, and proliferation index (Ki-67). Results: The average age was 45 years in early-stage and 58 years in advanced-stage patients. Early-stage tumors were smaller (average 1.5 cm), well-differentiated, hormone receptor-positive, and showed low Ki-67 proliferation. Advanced-stage tumors were larger (average 4-6.2 cm), poorly differentiated, with higher HER2 positivity, increased lymph node involvement, distant metastasis, and higher Ki-67 index. Radiologically, early tumors appeared as regular, hypoechoic masses with clear margins, while advanced tumors showed irregular shapes, necrosis, neovascularization, calcifications, and breast wall infiltration. Discussion: Significant radiological and clinicopathological differences exist between early and advanced breast cancer stages, reflecting tumor aggressiveness and progression. These findings align with previous studies emphasizing the importance of early detection and tailored treatment. Conclusion: Recognizing distinct features of early versus advanced breast cancer is essential for optimizing patient management. Further multicenter studies with larger cohorts are recommended to enhance understanding and improve outcomes.